Scintillation materials based on solid solutions ZnSxSe1–x - Trubaeva, O. G.; Chaika, M. A.; Galkin, S. M.; Lalayants, A. I.; Nepokupna, T. A. (Technology and design in electronic equipment, 2018)
Composite materials based on ZnSxSe1–x solid solutions are promising materials for gamma and X-ray detectors. However, influence of compositions and particle size on scintillation properties is unclear, which prevents their application. This paper reports on the complex study of microcrystalline ZnSxSe1–x powdered scintillations, prepared by solid phase synthesis from ZnS and ZnSe initial compounds. ZnSxSe1–x solid solutions were obtained in the range of x from 0.07 to 0.86 and in the following sizes: 200—250 μm, 140—200 μm, 140—80 μm, and less than 80 μm. X-ray diffractions of powder ZnSxSe1–x shows formation of a cubic lattice of sphalerite structure. ZnSxSe1–x powders demonstrate a presence of a luminescence band in the 590-615 nm regions, while an increase in sulfur concentration leads to a shift of the maximum intensity of X-ray induced luminescence to the short-wave region, which is associated with an increase of the band gap width. The best parameters of X-ray induced luminescence are obtained for the solid solution with 39 at.% of sulfur. The ZnS0,39Se0,61 solid solutions obtained under these conditions have an X-ray induced luminescence intensity that is 4 times higher than that of ZnSe(Al) single crystal and a relatively low level of afterglow. In ZnSxSe1–x solid solutions, increasing of particle size leads to shifts of the X-ray induced luminescence to the longwave region. The highest intensity of the X-ray induced luminescence corresponds to the ZnS0,39Se0,61 composition with the particle size of less than 80 μm. Also, ZnS0,39Se0,61 solid solutions, with particle size less than 80 microns, are more homogeneous in composition, which is why the process of solid phase reaction in them passes more efficiently. It is shown that the ZnSxSe1–x composite scintillators can be used as gamma and X-ray detectors. It has been established that the effectiveness of these materials depends on their composition. ZnS0,5Se0,5 and ZnS0,39Se0,61 composites demonstrate the best scintillation characteristics, with twice as high an efficiency as that of the «commercial» ZnSe(Al) composite.